2022
DOI: 10.3310/zowl2323
|View full text |Cite
|
Sign up to set email alerts
|

Shock-absorbing flooring for fall-related injury prevention in older adults and staff in hospitals and care homes: the SAFEST systematic review

Abstract: Background Injurious falls in hospitals and care homes are a life-limiting and costly international issue. Shock-absorbing flooring may offer part of the solution; however, evidence is required to inform decision-making. Objectives The objectives were to assess the clinical effectiveness and cost-effectiveness of shock-absorbing flooring for fall-related injury prevention among older adults in care settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 130 publications
(764 reference statements)
0
10
0
Order By: Relevance
“…According to the Shock-Absorbing Flooring Effectiveness SysTematic (SAFEST) review, some studies found shock-absorbent floors to dominate standard floors, which indicate lower costs and better outcomes. One study estimated that shock-absorbing floors increased both the cost and quality-adjusted life year; however, the quality of these studies is not high 25. The shock-absorbing flooring interventions have the potential to be cost-effective compared with standard flooring, while further research is required to determine whether shock-absorbing flooring is likely to increase the fall rate 26.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Shock-Absorbing Flooring Effectiveness SysTematic (SAFEST) review, some studies found shock-absorbent floors to dominate standard floors, which indicate lower costs and better outcomes. One study estimated that shock-absorbing floors increased both the cost and quality-adjusted life year; however, the quality of these studies is not high 25. The shock-absorbing flooring interventions have the potential to be cost-effective compared with standard flooring, while further research is required to determine whether shock-absorbing flooring is likely to increase the fall rate 26.…”
Section: Discussionmentioning
confidence: 99%
“…One study estimated that shock-absorbing floors increased both the cost and quality-adjusted life year; however, the quality of these studies is not high. 25 The shock-absorbing flooring interventions have the potential to be cost-effective compared with standard flooring, while further research is required to determine whether shock-absorbing flooring is likely to increase the fall rate. 26 Since reliable shock-absorbing performance and ease of mass production are important in terms of cost, the MM-flooring has a manufacturing style that is relatively easy to mass produce since the cushioning material is made of elastomer and manufactured in units of 500×500 mm area.…”
Section: Discussionmentioning
confidence: 99%
“…Adding our estimates to a recent meta-analysis that compared the effectiveness of sports floors with that of novel shockabsorbing floors, 19 the combined state of the clinical evidence suggests that compliant floors can reduce the risk of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they may provide similar injury-reducing effects at a lower cost, which has important implications for practice. However, the meta-analysis only contained two small-scale evaluations of sports floors, 19…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation